PENGARUH BOARD DIVERSITY , FIRM SIZE , PROFITABILITY, INSTITUTIONAL OWNERSHIP DAN LEVERAGETERHADAP EARNING QUALITY PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Andreas Bambang Daryatno; Linda Santioso (Universitas Kristen Krida Wacana, 2021)
The purpose of this study is to test empirically the effect of board diversity, firm size, profitability, institutional ownership and leverage on earning quality in manufacturing companies on the Indonesia Stock Exchange, especially in 2016-2018. The sampling technique in this study was purposive sampling method. Purposive sampling is a sampling technique using several predetermined criteria in accordance with the discussion so that it is feasible to be selected as a sample and 35 samples of manufacturing companies were selected with a total of 105 data. The analysis method used is panel data regression analysis with the help of the E – Views 9.0 program. The results of this study are board diversity, institutional ownership, leverage has no effect on earning quality, while firm size and profitability have an influence on earning quality. Keywords: board diversity , firm size , profitability, institutional ownership, leverage